Pengaruh Kinerja Guru dan Perhatian Orang tua terhadap Prestasi Siswa di Mts Miftahul Ulum Putri Ganjaran - Moh. Hifni Ramdhan; Muhammad Asrori; Jamilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to examine how parental involvement and teacher effectiveness affect kids' academic performance at MTs Raudlatul Ulum Putri Ganjaran. The study used a descriptive design and a quantitative methodology. There were 56 individuals in the population, all of whom were ninth-grade students and were included in the research sample. With the aid of SPSS version 20, data were gathered using a questionnaire with a Likert scale, and multiple linear regression techniques were used for the analysis. With a regression coefficient value of β = 0.290 and a significance level of 0.038 (< 0.05), the partial test (t-test) results show that teacher performance has a positive and statistically significant impact on students' academic attainment. However, there was no statistically significant effect of parental attention on teenagers' academic achievement, with a regression coefficient value of β = 0.128 and a significance level of 0.486 (> 0.05). However, with a F value of 4.596 and a significance level of 0.014 (< 0.05), the simultaneous test (F-test) results show that parental attention and teacher performance together have a statistically significant impact on students' academic attainment. Together, parental attention and teacher performance account for 14.8% of the variance in pupils' academic attainment, with other factors outside the research model influencing the remaining 85.2%, according to the coefficient of determination (R²) of 0.148. These results show that, especially in the setting of boarding-based madrasah education, where there is comparatively less direct connection between students and their parents, teacher effectiveness is the more significant factor impacting students' academic accomplishment.